Studying of Triangle Spread Function for Optical System includes Square Aperture and Compare with Circular Aperture , - A.B. Hassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
In this research: the triangle spread function (concluded from pupil function technique) has been regarded, to find image intensity from triangle object in optical system includes square aperture to compare with concluded values from (2.). The results shown that the square aperture contributes little Improvement on resolving power, and increases the depth of focus.